Economic analysis of sesame (Sesamum indicum L.) production in Northern Benin - Dossa, Kossivi Fabrice; Enete, Anselm Anibueze; Miassi, Yann Emmanuel; Omotayo, Abiodun Olusola (Frontiers in Sustainable Food Systems, 2023)
Introduction Sesame is an important cash crop that can be grown with limited resources. In recent decades it has drawn interests of many researchers and developers. This study analyzed the economics of Sesame (Sesamum indicum L.) produced in northern region of the Republic of Benin. Methods Structured questionnaire was used to gather primary data from 120 farmers who made up the sample size and were chosen using a multistage sampling technique. Data were analyzed using descriptive statistics, profitability analytical tools, multiple regression analysis and Likert scale rating technique. Profitability analytical tools were used to assess the economic performance of the sesame production; a multiple regression model was used to analyze factors that determine the output of the production in the study area; a 5-point Likert scale rating technique was utilized to rank the production's challenges according to farmers' observations. Results The findings revealed that sesame is mainly produced in sole cropping system and in rotation with other crops. The net farm income analysis showed that sesame farming was a profitable venture in the study area. The study also showed that factors like age, household size, crop rotation, and capital input influence the revenue of sesame production. While age, household size and capital input have a beneficial and significant influence on the farms' net revenue from sesame produce, crop rotation has a negative effect on it. Amongst the various constraints identified, the most significant ones are access to labor and land, uneven ripening, lack of storage facilities and access to improved seed. Discussion Based on these results, authorities in agricultural sector should develop and promote this value chain at the national level as it will greatly boost the country's economy.